Comparative Analysis of Seller's Preferences in Selling Online in Marketplaces - Putri, Arinda Soraya; Setiono, Muklis (TALENTA Publisher, 2023)
In Indonesia, the growth of internet commerce (e-commerce) tendencies has nearly doubled since the Covid-19 pandemic. The changes that have taken place have created a pattern where individuals are switching from traditional to internet buying. Both Shopee and Tokopedia provide business actors numerous options to boost sales, but each e-commerce has advantages and disadvantages specific to the services offered to business actors in e-commerce. This study compares Shopee and Tokopedia sellers' perceptions of their experiences to see if there are any discrepancies. In order to collect data, preference and comparison problem-related questionnaires were sent. Shopee excels in the people variable, while Tokopedia excels in the product, price, site, promotion, physical facilities, and process factors, according to the average perceived value of each variable. Overall, Tokopedia outperforms Shopee in terms of the services it offers to merchants. The findings of this study can be utilized to assess the issues that arise from comparison studies in order to better the research subject.